A Comment on "How Wage Announcement Affect Job Search - A Field Experiment" - Justin Dang; Nicolas Maeder; Chenyu Mao; Kwanjai Yoo (Institute for Replication (I4R), 2025)
This report replicates the study by Belot et al. (2022), which investigates how posted wages affect labor supply through a field experiment using a job platform with varying wage postings. The paper's main finding is that a higher wage increases job seekers' interest in a vacancy, a result at odds with the same variables' inverse relationship in the paper's observational data. This report assesses the computational and robustness reproducibility of the referenced paper's results. Testing various empirical specifications and datasets, we find that all findings are, in fact, reproducible. Most importantly, the elasticity of a job posting's saves/views with respect to its posted wage is consistently positive and statistically significant across all of our specifications and datasets.
Keywords: 330